Advanced Platelet‐Rich Fibrin in Periosteal Inversion Technique for Root Coverage: A Case Report. Issue 4 (25th August 2020) - Chellathurai, Burnice Nalina Kumari; Ganesh, Balaji; Rajaram, Vijayalakshmi
Abstract : Introduction: The management of gingival recession associated with esthetic concerns and root hypersensitivity is challenging, and its sequelae is based on the assessment of etiological factors and the degree of tissue involvement. Procedures using pedicle flaps, free soft tissue grafts, combination of pedicle flaps with grafts, barrier membranes, and the use of platelet concentrates are all effective for this purpose. The use of the third‐generation platelet concentrate, advanced platelet‐rich fibrin (A‐PRF), has evolved as a promising regenerative material for root coverage procedure wherein it acts as a scaffold and also accelerates wound healing due to its dense fibrin meshwork. Case Presentation: This case report, discusses treating an isolated maxillary Miller Class I recession in a 25‐year‐old male patient by a periosteal inversion method along with the A‐PRF membrane. A partial thickness flap was reflected; periosteum was inverted; and an A‐PRF membrane was placed over the denuded root surface which aided in enhanced regeneration; 100% root coverage was obtained as seen in follow‐up visits. Conclusion: The periosteal inversion technique along with an A‐PRF membrane seems to be a novel approach in managing an isolated Miller Class I maxillary gingival recession.